A perceptual study of language chunking in Estonian - Ots Nele; Taremaa Piia (Open Linguistics, 2022)
Two studies investigate the production and perception of speech chunks in Estonian. A corpus study examines to what degree the boundaries of syntactic constituents and frequent collocations influence the distribution of prosodic information in spontaneously spoken utterances. A perception experiment tests to what degree prosodic information, constituent structure, and collocation frequencies interact in the perception of speech chunks. Two groups of native Estonian speakers rated spontaneously spoken utterances for the presence of disjunctures, whilst listening to these utterances (N=47N=47) or reading them (N=40N=40). The results of the corpus study reveal a rather weak correspondence between the distribution of prosodic information and boundaries of the syntactic constituents and collocations. The results of the perception experiments demonstrate a strong influence of clause boundaries on the perception of prosodic discontinuities as prosodic breaks. Thus, the results indicate that there is no direct relationship between the semantico-syntactic characteristics of utterances and the distribution of prosodic information. The percept of a prosodic break relies on the rapid recognition of constituent structure, i.e. structural information.